Airborne Particulates Relationship With Ambient Temperature And Relative Humidity In Determining Soiling Defects On The Artefacts At The National Museum, Kuala Lumpur, Malaysia - Muhsin Kolapo, Otuyo; Mohd Din, Shamzani Affendy; Osman, Sharina; Azam Adnan, Muhamad; Jawahir Raduian, Nor (Opción, 2019)
Artefacts in the Museum are continuously exposed to adverse climatological conditions such as the high concentration of Particulate Matter, unstable Tem- perature and Relative Humidity. These adverse climatological conditions can cause varieties of mechanical, chemical and biological damages to the exhibits in a museum and cultural heritage building collections. Thus, this research is aimed at determining the airborne particulates relationship with the ambient temperature and relative humidity in relation to the soiling defects towards the artefacts in Gallery A and Gallery B of the National Museum, Kuala Lum- pur, Malaysia. The researchers collected data for 40 days. The microclimate results show that there is an unwanted variability in most of the sample sta- tions during the period of this research. The variation can cause several damages to artefacts present in both Gal- leries. Most of the Temperature and Relative Humidity results in Gallery B were beyond the acceptable limits with the location of indoor area and unglazed ceramic exhibition box falling 16 % above ASHRAE fluctuation limit for Relative Humidity. However, the values of Relative Humidity at all sample locations were observed to be within limits set by Italian Stand- ard (UNI 10829/99). In Gallery A, a strong negative correlation of 0.6 and 0.7 were observed between the average Temperature and respirable mass concentration, and average Temperature and Total inhalable mass concentration, consecutively, although a relatively positive relationship of 0.5 was observed between average Relative Humidity and respective mass concentration values. In contrary to Gallery A’s results, the relationship between the mass concentration of respirable and total inhalable Partic- ulate matters and T and RH observe in Gallery B, shows a weak positive and negative relationship in some cases and no relationship in others. The research concludes that the climatological conditions of Gallery A and Gallery B of the National Museum Malaysia are in the worst condition and urgent attention needs to be arranged to negate the possibility of its effects.